2012
DOI: 10.1088/0963-0252/21/5/055008
|View full text |Cite
|
Sign up to set email alerts
|

Partial constriction in a glow discharge in argon with nitrogen admixture

Abstract: The constriction of the positive column of a glow discharge in argon with nitrogen admixture (0.02-1%) was studied. The discharge was maintained in a tube of 2.8 cm inner diameter and 75 cm length at intermediate pressures (several tens of Torrs), at which the discharge constriction goes by a jump and the hysteresis effect is well pronounced. It was observed that the constriction begins near one of the electrodes and then the constricted region boundary propagates toward the other electrode. The reverse transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
(51 reference statements)
3
18
0
Order By: Relevance
“…Presently, 1D models of current contraction in a tube are well developed. They take into account the kinetics of electrons, ions, and metastable particles, and provide reasonable agreement with the experiments [4][5][6][7][8].…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Presently, 1D models of current contraction in a tube are well developed. They take into account the kinetics of electrons, ions, and metastable particles, and provide reasonable agreement with the experiments [4][5][6][7][8].…”
supporting
confidence: 69%
“…Presently, 1D models of current contraction in a tube are well developed. They take into account the kinetics of electrons, ions, and metastable particles, and provide reasonable agreement with the experiments [4][5][6][7][8].There are a number of experiments stimulated by the development of powerful gas-discharge lasers and plasma-chemical reactors (see review [9]) where the current contraction phenomenon was observed when the discharge power exceeds a certain threshold level. However, this phenomenon in a plane duct in the presence of the gas flow is not well understood.…”
supporting
confidence: 62%
“…It was observed that at intermediate pressures a small additive of nitrogen to argon resulted in a noticeable decrease in the discharge voltage of a diffuse dc discharge. This effect was discovered in experiments with partially constricted discharges in Ar:N 2 mixtures [15,16,34]. Figure 2 shows current-voltage characteristics measured in pure argon and in Ar + 0.75%N 2 and Ar + 1%N 2 gas mixtures at gas pressure P = 40 Torr (R = 1.4 cm, interelectrode distance ≈ 75 cm).…”
Section: Influence Of N 2 Admixture On the Current-voltage Characterimentioning
confidence: 72%
“…At the same time, VACs in the constricted region go approximately along the same curve. As is shown in [16], it can be explained by the fact that, due to a very high electron density in a constricted discharge, N2 addition has very little influence on ionization mechanism which in Ar and Ar-N2 cases is mainly stepwise ionization of Ar metastables.…”
Section: Effect Of Nitrogen Addition To Argon On Discharge Constrictimentioning
confidence: 98%
See 1 more Smart Citation